Development of the Population and Settlement Structures in the Pilsen Region and Marginal Areas - Matušková, Alena (Journal for Geography, 2006)
This article discusses the development of inhabitants and the settlement structure in the Pilsen district of the Czech Republic. It focuses on both the current situation in Pilsen and its metropolitan area as well as on developments in small towns and peripheral areas. The article highlights the main features and disparities in development. It points out negative development trends in peripheral areas, which should be addressed by national and regional institutions.
Keywords: population; settlement structures; Pilsen district; metropolitan areas; peripheral areas